Addressing the Data Linking Challenges - Valentic, Maja; Plese, Borna; Pristas, Ivan; Ivankovic, Damir (Methods of Information in Medicine, 2017)
Background: PARENT JA (cross-border Patient Registries iNiTiative Joint Action), a joint EU and Member States project, has conducted a research among EU patient registries aimed at gathering information on the registries’ interoperability readiness. Leaning on the information and data collected through the previous PARENT JA research, this study aims to provide more detailed view into the registry holders’ practical challenges with data linking. Since the studies which dealt with patient data exchange have often neglected the registry holders’ performance of data exchange, we wanted to put a spotlight on various EU registry holders’ practices and operations, aiming to detect their needs and concerns in the process of running an interoperable registry. The focus of this study was identifying the main practices and challenges in patient registries interoperability improvement.Methods: The basis for this analysis were the data collected in the series of structured interviews. The size of the interview sample was 13 patient registries, each from a different EU country. The structured interview consisted of nine questions and was conducted in two parts: oral and written. The answers were analysed using open coding.Results: Results are interpreted in the context of the six main themes that emerged through a comprehensive analysis. (1) Examples of data exchange: The most common reported data exchange practices were seen only as a way to achieve the most immediate needs and interests of the individual registries. (2) Awareness and use of international standards: International data and clinical standards were not widely used by the interviewed registries. (3) Use of data models and formats: In the area of data models and formats there is no universally used practice. (4) Data request protocols and procedures: Procedures and protocols varied, mostly depending on the national legal systems in which the patient registries operated. (5) Data security and integrity: Security of personal data was a universal concern for all registry holders that were interviewed; identifiable individual data was shared only in one case. (6) Opportunities and challenges of registry interoperability: most registry holders responded that their registries were well prepared for interoperability practices and that data exchange has never been their primary operative concern.Conclusions: Most of the difficulties regarding data linking were not necessarily associated with technical issues, which registry holders listed outright. Our analysis showed that the lack of interoperability came as a result of organizational or legal constraints that made the registries unable to process and conduct data linking quickly and effectively with other sources.
Keywords: Registries; health information exchange; patient data privacy; attitude of health personnel